Study of morphometric changes of cornea in cases of pterygium - Kumar, Mukesh; Farooq, Shaheen; Khan, Nabab A.; Kochar, Anju; Sunda, Prinyanka (International Journal Of Community Medicine And Public Health, 2023)
Background: Pterygium is a benign, wing-shaped, fibrovascular growth that originates on the bulbar conjunctiva and can spread to the limbus and beyond, causing morphometric changes in the cornea and affecting visual status. Aim of study was to study the morphometric changes in the cornea in patients with pterygium. Methods: Prospective hospital-based analytical study conducted on 100 consecutive patients with unilateral pterygium for two years. Each patient underwent a complete ophthalmic examination, including evaluation of visual acuity refraction, corneal curvature, corneal endothelial cell density (CECD), central corneal thickness (CCT), coefficient of variation (CV) and hexagonality. Necessary demographic data and variables like age, smoking status and occupation were also determined. The healthy eye was considered as a control. Results: Majority of the study population, i.e. 43%, belonging to the 21-40 years of age group; socioeconomically, maximum cases (61%) were found in class IV with a male preponderance of 53%. 56% of patients hailed from rural areas, and regarding occupation, it was found that 37% of patients were farmers. This study found that the majority of patients (60% of cases) had multiple ocular complaints. There was a significant association between pterygium grade and keratometric astigmatism. Our study found a significant difference between ECD, hexagonality and CV in the normal and diseased eye. CCT was found more in diseased eyes but was significant only in grade IV pterygium. Conclusions: Pterygium leads to deterioration of visual performance by causing refractive and keratometric changes.